(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2012)
The Emotional Stroop task has been used with remarkable frequency in recent years and is the most often used task of assessing the attentional bias in experiments for this purpose. This study aimed to compare the attentional bias toward emotional words in individuals with different levels of state and trait anxiety using the Emotional Stroop task. Participants were undergraduate students (n=111, M=21.6 years) who responded to the STAI. In the Emotional Stroop task, were used 20 pairs of words with high activation and negative valence, and matched controls with neutral images, coming from the Affective Norms for English Words (ANEW). Although the Stroop effect in this sample was partly observed, these results indicated that trait and state anxiety are not important to the attentional bias toward negative stimuli with high levels of activation.